EDUCATIONAL TECHNOLOGY ON URINARY TRACT INFECTION FOR RIVERINE PREGNANT WOMEN: SHARED CONSTRUCTION - Neves, Paula Victória Tiribaxi; Rodrigues, Ivaneide Leal Ataíde; Pereira, Alexandre Aguiar; Andrade, Erlon Gabriel Rego de; Nogueira, Laura Maria Vidal; Maia, Richer Praxedes; Moraes, Carlos Marcelo da Silva (Cogitare Enfermagem, 2023)
Objective: to build, in a shared way, an educational technology about urinary tract infection for riverine pregnant women in Primary Health Care. Method: qualitative methodological research, developed with 24 pregnant women enrolled in prenatal care at a Family Health Unit on the island of Combú, in Belém, Pará, Brazil. The data were produced in the period from February to August 2021, through individual interviews and conversation circle, and were submitted to content analysis, originating the themes to build the technology. Results: two thematic categories were organized, inherent to the knowledge of riverine pregnant women about urinary tract infection and their hygiene practices to prevent this grievance. The categories subsidized the elaboration of a folder, chosen by them, adding relevant information, with illustrations and easy-to-understand language. Conclusion: it was evidenced that the pregnant women’s knowledge on the theme and health care practices need to be strengthened.